PENGARUH MODEL KUNJUNGAN GALERI TERHADAP KEMAMPUAN 4C SISWA DALAM PEMBELAJARAN CERPEN - WENI, ERMAWENI; Syofiani, Syofiani; Fikri, Hasnul (JELISA (Jurnal Edukasi dan Literasi Bahasa), 2024)
The research entitled "The Influence of the Gallery Visit Model on Students' 4C Ability in Short Story Learning" was motivated by students' lack of interest in short story learning. This happens because teachers have not been able to use appropriate learning models for learning short story texts. The aim of this research is to see whether the use of the gallery visit model can influence students' 21st century skills, namely what is known as 4C (Cerative, Communicative, collaborative and critical). This research uses a qualitative approach with a quasi-experimental method. In this research, data was obtained that the classes that received treatment showed an increase in 4C abilities compared to classes that did not receive treatment.